A comparison of operative outcomes between standard and robotic laparoscopic surgery for endometrial cancer: A systematic review and meta‐analysis. Issue 4 (1st August 2017) - Ind, Thomas; Laios, Alex; Hacking, Matthew; Nobbenhuis, Marielle
Abstract: Background: Evidence has been systematically assessed comparing robotic with standard laparoscopy for treatment of endometrial cancer. Methods: A search of Medline, Embase and Cochrane databases was performed until 30th October 2016. Results: Thirty‐six papers including 33 retrospective studies, two matched case–control studies and one randomized controlled study were used in a meta‐analysis. Information from a further seven registry/database studies were assessed descriptively. There were no differences in the duration of surgery but days stay in hospital were shorter in the robotic arm (0.46 days, 95%CI 0.26 to 0.66). A robotic approach had less blood loss (57.74 mL, 95%CI 38.29 to 77.20), less conversions to laparotomy (RR = 0.41, 95%CI 0.29 to 0.59), and less overall complications (RR = 0.82, 95%CI 0.72 to 0.93). A robotic approach had higher costs (1746.20, 95%CI 63.37 to 3429.03). Conclusion: A robotic approach has favourable clinical outcomes but is more expensive.